Legal Analysis of Corporate Social Responsibility (CSR) for Labor From the Perspective of Investors and Capital Markets - Yusuf Akbar Khairulah (Jurnal Multidisiplin Sahombu, 2026)
The implementation of Corporate Social Responsibility (CSR) in labor aspects has become a key element in modern business practices, which focus not only on profits but also on worker welfare and social sustainability. In Indonesia, although there are legal foundations related to CSR, such as the Company Law and the Capital Market Law, the implementation of labor-related CSR still faces several challenges, especially concerning transparency and weak oversight. Proper labor CSR implementation can strengthen a company’s reputation and attract investors, while labor violations risk decreasing stock values and damaging the company’s reputation. Therefore, to protect investors and create a transparent capital market, legal reforms are necessary to support clearer labor CSR reporting, as well as strengthening the role of the Financial Services Authority (OJK) and the Indonesia Stock Exchange in oversight.